The Phosphatase PP2A Interacts With ArnA and ArnB to Regulate the Oligomeric State and the Stability of the ArnA/B Complex - Ye, Xing; Vogt, Marian Samuel; van der Does, Chris; Bildl, Wolfgang; Schulte, Uwe; Essen, Lars-Oliver; Albers, Sonja-Verena (Frontiers in Microbiology, 2020)
In the crenarchaeon Sulfolobus acidocaldarius, the archaellum, a type-IV pilus like motility structure, is synthesized in response to nutrient starvation. Synthesis of components of the archaellum is controlled by the archaellum regulatory network (arn). Protein phosphorylation plays an important role in this regulatory network since the deletion of several genes encoding protein kinases and the phosphatase PP2A affected cell motility. Several proteins in the archaellum regulatory network can be phosphorylated, however, details of how phosphorylation levels of different components affect archaellum synthesis are still unknown. To identify proteins interacting with the S. acidocaldarius phosphatases PTP and PP2A, co-immunoprecipitation assays coupled to mass spectrometry analysis were performed. 30 minutes after growth in nutrient starvation medium, especially a conserved putative ATP/GTP binding protein (Saci_1281), a universal stress protein (Saci_0887) and the archaellum regulators ArnA and ArnB were identified as highly abundant interaction proteins of PP2A. The interaction between ArnA, ArnB and PP2A was further studied. The ArnA/B heterodimer was reconstituted from the purified proteins. In complex with ArnA, phosphorylation of ArnB by the ArnC kinase was strongly stimulated and resulted in formation of (ArnA/B)2 and higher oligomeric complexes, while dephosphorylation by PP2A resulted in dissociation of these ArnA/B complexes.